2010
DOI: 10.1192/bjp.bp.109.070409
|View full text |Cite
|
Sign up to set email alerts
|

Cohort-specific risk of suicide for different mental disorders in China

Abstract: The suicide risk associated with mental illness varies by type of illness and by demographic cohort. Lower risk of suicide among rural residents with mental disorders highlights the importance of non-mental health approaches to the prevention and management of suicidal behaviour in rural areas of low- and middle-income countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
27
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 26 publications
4
27
0
Order By: Relevance
“…The finding of a history of mental illness as an independent risk factor for suicide in our study is consistent with some studies in China [6,32,34] and Western countries [7,[54][55][56] . In Western cultures, psychological autopsy studies revealed that 90-95 percent of suicide victims had a diagnosable psychiatric disorder at the time of the suicide [1] , but only about half of suicide victims in China had a history of psychiatric diagnosis at the time of death [4,6,32,34] .…”
Section: Issn 2372-5923supporting
confidence: 81%
See 4 more Smart Citations
“…The finding of a history of mental illness as an independent risk factor for suicide in our study is consistent with some studies in China [6,32,34] and Western countries [7,[54][55][56] . In Western cultures, psychological autopsy studies revealed that 90-95 percent of suicide victims had a diagnosable psychiatric disorder at the time of the suicide [1] , but only about half of suicide victims in China had a history of psychiatric diagnosis at the time of death [4,6,32,34] .…”
Section: Issn 2372-5923supporting
confidence: 81%
“…In Western cultures, psychological autopsy studies revealed that 90-95 percent of suicide victims had a diagnosable psychiatric disorder at the time of the suicide [1] , but only about half of suicide victims in China had a history of psychiatric diagnosis at the time of death [4,6,32,34] . The decline in suicide has been reported in United Kingdom and the United States although the role of the treatment of psychiatric disorders in the decline of suicide remains unclear [11,57] .…”
Section: Issn 2372-5923mentioning
confidence: 99%
See 3 more Smart Citations